Water-based PEKC-COOH sizing agent for enhancing the interfacial adhesion of carbon fiber/polyether-ether-ketone composites. (15th November 2021) - Hu, Jiaoli; Yan, Fei; Liu, Hao; Zhao, Lianshuang; Li, Zheng; Liu, Yu; Ao, Yuhui; Liu, Liu
Abstract: Improving the dissatisfactory interfacial adhesion of carbon fiber (CF)/polyether-ether-ketone (PEEK) composites in some specific conditions is an extremely urgent demand. In this work, a series of soluble phenolphthalein polyaryl-ether-ketone polymers with different carboxyl contents (PEKC-COOH) were synthesized and employed to prepare water-based sizing agents. PEKC-COOH showed high solubility and excellent thermal properties, with over 239.5 °C of Tg value, which were much higher than that of PEEK (148.4 °C). The sizing agents exhibit good storage stability with particle sizes between 60.6 and 75.0 nm. Compared to unsized CF/PEEK composites, the bending strength and interlaminar shear strength of the CF-5/PEEK composites were enhanced by 52.9% and 53.3%, respectively. An illustrative mechanism for the interfacial reinforcement effect of the sizing agent was proposed accordingly. The protocol provides an effective and green method towards water-based sizing agent for enhancing the interfacial properties of CF/PEEK composites.